Liberia's Infrastructure : A Continental Perspective - Foster, Vivien; Pushak, Nataliya (2012)
Liberia's power generating capacity and national grid were completely demolished during 14 years of civil war. Piped water access fell from 15 percent of the population in 1986 to less than 3 percent in 2008. War also left the national road network in a state of severe disrepair. Since the return of peace, the port of Monrovia has resumed normal operations under private management, and progress has been made in securing donor finance for road reconstruction. Liberia has also successfully liberalized its mobile telephone markets, with low-priced access surging to 40 percent in 2009. Liberia's starkest challenge lies in funding a more cost-effective power sector. The country's generation capacity is barely one-tenth of the benchmark level of Africa's other low-income countries. The cost of generating power is exorbitant, and the power tariff is three times the regional average. Addressing Liberia's public infrastructure needs will require sustained expenditures of between $350 million and $600 million annually, mostly to fund power and transport. In the mid-2000s, with all sources of spending taken into account, Liberia spent around $90 million a year on infrastructure. An additional $17 million was lost to inefficiencies, such as underpricing of power. Because Liberia suffers an annual funding gap of between $250 million and $500 million per year, it will need a combination of increased finance, improved efficiency, and cost-reducing innovations to reach its infrastructure targets in a reasonable time. Without these, Liberians may have to wait for up to 40 years to achieve the targets.